Phytochemical compounds of Pangium edule Reinw. seeds - Liam, Jack; Ibrahim, Faridah Hanum; Hakeem, Khalid Rehman (Faculty of Forestry, Universiti Putra Malaysia, 2013)
Pangium edule seeds are widely used as a source for cooking oil, vegetable and fish or meat preservative among the local communities in Sarawak and Sabah. Isolation and determination of chemical components were carried out on P. edule seeds. Biological activity tests revealed that the samples were not toxic. Three components, namely, Hexadecanoic acid, Heptadecene-(8)-Carbonic acid and 9,12-Octadecedienoic acid were determined by a series of procedures viz: cold extraction, thin layer chromatography (TLC), gas chromatography (GC) and gas chromatography-mass spectroscopy (GC-MS). The phytochemical compounds of P. edule seeds indicate their potential for commercialisation especially in the food industry.